2009
DOI: 10.1093/brain/awp142
|View full text |Cite
|
Sign up to set email alerts
|

The neurophysiological correlates of motor tics following focal striatal disinhibition

Abstract: The cortico-basal ganglia pathway is involved in normal motor control and implicated in multiple movement disorders. Brief repetitive muscle contractions known as motor tics are a common symptom in several basal ganglia related motor disorders. We used focal micro-injections of the GABA-A antagonist bicuculline to the sensorimotor putamen of behaving primates to induce stereotyped tics similar to those observed in human disorders. This focal disruption of GABA transmission in the putamen led to motor tics conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
124
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 56 publications
13
124
2
Order By: Relevance
“…The general rationale for modulating (or ablating) these areas is based on the assumption that tics and abnormal behaviour are associated with dysfunction of corticostriatal-thalamocortical circuitry involving frontal associative and limbic areas of the basal ganglia and thalamus (Table 2). Focal disruption of different functional striatal territories results in abnormal activation of neocortical motor and non-motor areas, producing repeated stereotypical movements and elaborated stereotypical behaviour, which supports the notion that both tics and OCD in GTS are related to BG-thalamocortical loop dysfunction [83][84][85][86][87]. Anecdotal improvements in GTS patients treated with DBS have been reported, but controlled studies currently include only very small numbers of patients [88,89].…”
Section: Dbs In Psychiatrymentioning
confidence: 57%
“…The general rationale for modulating (or ablating) these areas is based on the assumption that tics and abnormal behaviour are associated with dysfunction of corticostriatal-thalamocortical circuitry involving frontal associative and limbic areas of the basal ganglia and thalamus (Table 2). Focal disruption of different functional striatal territories results in abnormal activation of neocortical motor and non-motor areas, producing repeated stereotypical movements and elaborated stereotypical behaviour, which supports the notion that both tics and OCD in GTS are related to BG-thalamocortical loop dysfunction [83][84][85][86][87]. Anecdotal improvements in GTS patients treated with DBS have been reported, but controlled studies currently include only very small numbers of patients [88,89].…”
Section: Dbs In Psychiatrymentioning
confidence: 57%
“…Specifically, structural and functional imaging studies have found abnormalities in the striatum (Singer and Minzer, 2003), which is the main input structure of the basal ganglia (BG). The direct involvement of the striatum in tics is further supported by findings that disruption of striatal information transmission by localized application of a GABA A antagonist induces motor tics (Tarsy et al, 1978;Crossman et al, 1988;McCairn et al, 2009;Worbe et al, 2009).…”
Section: Introductionmentioning
confidence: 76%
“…In two cynomolgus monkeys, focal disinhibition of the sensorimotor putamen, using the GABA A antagonist bicuculline, produced repetitive motor tics predominantly in the orofacial region (McCairn et al, 2009). Local field potential spikes, which correlated with tics, were identified throughout the cortico-basal ganglia pathway.…”
Section: Monkey Focal Striatal Disinhibitionmentioning
confidence: 97%